THE ROLE OF INTELLECTUAL CAPITAL AS A MODERATION OF CORRELATIONS BETWEEN ECONOMIC VALUE ADDED (EVA) AND MARKET VALUE ADDED (MVA) ON STOCK RETURNS - Prasetyo Wibowo, Yudhi; Djaddang, Syahril; Darmansyah, Darmansyah (EDUTECH CONSULTANT, 2018)
This research aims to examine and analyze the influence of economic value added (EVA) and market value added (MVA) toward stock return, through intellectual capital as mediation. The time period in this study was taken between 2011-2015. The sample in this research using purposive sampling method amounted to 27 companies listed on the Stock Exchange. The analysis technique used is moderated regression analysis. This study shows some of the results. Both economic value added (EVA) and market value added (MVA) havepositive and significant effects on stock return and also Intellectual Capital is able to strengthen EVA's and MVA’s positive relationship with stock returns.